2019
DOI: 10.1029/2018gb006140
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Controls on the Riverine Export of Dissolved Black Carbon

Abstract: Each year, tropical rivers export a dissolved organic carbon (DOC) flux to the global oceans that is equivalent to ~4% of the global land sink for atmospheric CO2. Among the most refractory fractions of terrigenous DOC is dissolved black carbon (DBC), which constitutes ~10% of the total DOC flux and derives from the charcoal and soot (aerosol) produced during biomass burning and fossil fuel combustion. Black carbon (BC) has disproportionate storage potential in oceanic pools and so its export has implications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 171 publications
(446 reference statements)
0
24
2
Order By: Relevance
“…Nonetheless, most studies have failed to identify significant seasonality in the DBC content of DOC, including in major high-latitude rivers 48 , tropical rivers and temperate catchments 51,56 . Soil moisture, a proxy for seasonal hydrology, was also not found to be a significant driver of variability in the DBC content of DOC in tropical Brazilian rivers 42 . We verified that the differences in the DBC content of DOC across latitudes and biomes are not due to bias in the timing of sample collection.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…Nonetheless, most studies have failed to identify significant seasonality in the DBC content of DOC, including in major high-latitude rivers 48 , tropical rivers and temperate catchments 51,56 . Soil moisture, a proxy for seasonal hydrology, was also not found to be a significant driver of variability in the DBC content of DOC in tropical Brazilian rivers 42 . We verified that the differences in the DBC content of DOC across latitudes and biomes are not due to bias in the timing of sample collection.…”
Section: Resultsmentioning
confidence: 79%
“…Riverine dissolved black carbon (DBC) is chiefly a by-product of the decomposition of soil BC stocks, which are maintained by landscape fires and by small aerosol fluxes to the land surface 41,42 ( Fig. 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…lack carbon (BC), a common residue of incomplete combustion of biomass and fossil fuel, is widely dispersed in soils and marine sediments 1,2 . Defined as a group of condensed byproduct chemicals, BC is thought to be chemically stable and hardly biodegradable 3,4 , thus representing a refractory fraction of organic carbon (OC), and its role in the global carbon cycle and its environmental impacts have received considerable attention 2,[5][6][7][8] . In recent years, several studies have reported that dissolved BC (DBC) could represent a significant fraction of BC mobilized and transported by rivers into the ocean [9][10][11][12] .…”
mentioning
confidence: 99%